2016
DOI: 10.1016/j.nutres.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma endocannabinoids and appetite in hemodialysis patients: A pilot study

Abstract: Uremia-associated anorexia may be related to altered levels of long chain n-6 and n-3 polyunsaturated fatty acid (PUFA) derived circulating endocannabinoids (EC) and EC-like compounds that are known to mediate appetite. Our study's hypothesis was that such molecules are associated with appetite in patients with end-stage renal disease. A cross-sectional observational study was performed in 20 chronic hemodialysis patients (9 females, 11 males) and 10 healthy female controls in whom appetite was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
(28 reference statements)
0
17
1
Order By: Relevance
“…In this regard, data on the association of endocannabinoids with clinical and laboratory markers are very limited in patients with ESRD. The only available report is a study by Friedman et al [23] , which did not find any differences in plasma (EDTA-preserved tubing) endocannabinoid levels between healthy controls and patients with ESRD. However, it should be noted that the small sample size (n = 20), significant sex differences between the control and ESRD groups, and use of plasma (vs our samples which were serum) in their study make interpretation and comparison with our study difficult [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, data on the association of endocannabinoids with clinical and laboratory markers are very limited in patients with ESRD. The only available report is a study by Friedman et al [23] , which did not find any differences in plasma (EDTA-preserved tubing) endocannabinoid levels between healthy controls and patients with ESRD. However, it should be noted that the small sample size (n = 20), significant sex differences between the control and ESRD groups, and use of plasma (vs our samples which were serum) in their study make interpretation and comparison with our study difficult [23].…”
Section: Discussionmentioning
confidence: 99%
“…The only available report is a study by Friedman et al [23] , which did not find any differences in plasma (EDTA-preserved tubing) endocannabinoid levels between healthy controls and patients with ESRD. However, it should be noted that the small sample size (n = 20), significant sex differences between the control and ESRD groups, and use of plasma (vs our samples which were serum) in their study make interpretation and comparison with our study difficult [23]. Our study evaluated serum endocannabinoid levels in a large cohort of patients with ESRD who were compared with age- and sex-matched healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that plasma endocannabinoids are a result of spill-over from tissues like the brain and gut (Hill et al, 2008;Matias et al, 2012), however, it is unknown to what extent plasma concentrations reflect endocannabinoid concentrations in these other tissues. A previous study suggested a link between plasma endocannabinoid concentration and feelings of appetite (Friedman et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…These markers should respond to nutrient and caloric intake, but not to the palatability of the food. To further elucidate the post-ingestive endocannabinoid response, we not only measured AEA, 2-AG, OEA and PEA, but included three more endocannabinoid-related compounds that have been suggested to be relevant for food intake or induce cannabinomimetic behavioural effects, namely stearoylethanolamide (SEA; Terrazzino et al, 2004), dihomo-γ-linolenoylethanolamide (DLE; Barg et al, 1995), and docosahexaenoylethanolamide (DHEA; Barg et al, 1995;Friedman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%